Positive psychology for healthcare professionals : a toolkit for improving wellbeing - Macfarlane, Jan; Carson, J. (Emerald Publishing Limited, 2023)
There has been an abundance of research carried out relating to the use of positive psychology, but a focus on staff working in care settings has been lacking. Positive Psychology for Healthcare Professionals presents applied positive psychology specifically for health and care staff, showcasing eleven different interventions that have proven to be effective in improving wellbeing. Positive Psychology Interventions are validated techniques, developed to include wellbeing enhancing activities, building effective user-friendly, cost-effective self-help strategies. This toolkit for improving wellbeing provides a more holistic roadmap to increase self-awareness of staff abilities, potential talents, and positive characteristics, through a strengths-based approach.
Keywords: Positive psychology.; Well-being.; Medical personnel.; Psychology -- General.; Psychology.; elektronické knihy; electronic books